Triglyceride Glucose Index as a Predictor of 30-Day Readmission and 6 Months Mortality After Hospitalization in Acute Decompensated Heart Failure - Rezeki, Arindya; Widyantoro, Bambang; Rossimarina, Vienna; Dwiputra, Bambang; Danny, Siska Surinanda; Sukmawan, Renan; Santoso, Anwar (The Indonesian Heart Association, 2025)
In “Triglyceride Glucose Index as a Predictor of 30-Day Readmission and 6 Months Mortality After Hospitalization in Acute Decompensated Heart Failure” (Indonesian Journal of Cardiology, 44(2), 53-60. https://doi.org/10.30701/ijc.1380), there are an errors noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1380. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. An error also occurred in the author’s name. We have corrected the author’s name from “Vienna Rossiamarina” to “Vienna Rossimarina.” There is also an error in the page numbering on the first page of the article. At the top, it says “57-64,” but we have changed it to the correct page numbers (53-60). The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1380